Analysis of the Concept of Multicultural Education According to KH. Abdurahman Wahid (Gus Dur) - Desiana, Desiana; Adinda, Charisma; Hafifatul Mukarohmah, Ayun; Dimas, Dimas; Tajudin, Nilawati; Sagala, Rumadani; Abas, Erjati (Jurnal Multidisiplin Indonesia, 2024)
The plurality of society in Indonesia is one of the icons of Indonesia. With plurality, people are expected to respect differences in ethnicity, race, religion, and culture. However, plurality must be the basis of community tolerance, rarely causing conflicts due to differences. The emergence of conflicts that occur is one of the indicators that Indonesian people still do not fully understand the problem of multicultural internal conditions. Gus Dur's presence in advancing multicultural education emerged as part of a response to the phenomenon of ethnic, racial, religious, and cultural differences that often arise in the midst of a multicultural society. Gus Dur's concept of multicultural education emphasizes on cultivating a life of respect and tolerance for diversity that lives in a pluralistic society and fostering generations who are not only knowledgeable and skilled, but also able to live together in society as the nation's successor. This study uses literature research by reviewing several Gus Dur books. The results of the study show that there are differences in religion, race, and culture that do not conflict with each other and are not a source of division in society. So that multicultural Islamic education is a very urgent thing to be carried out to bring flexibility and openness to each other.